Histopathology of bladder carcinomas: an eight year retrospective study at Lagos state university teaching hospital, Ikeja, Nigeria - Sanni, Daniel A.; William, Oluwaseun O.; Soyemi, Sunday S.; Abolarinwa, Abimbola A.; Popoola, Abiodun O. (International Journal of Research in Medical Sciences, 2020)
Background: This study was undertaken to evaluate the histological types, frequency, age and sex distribution of bladder carcinoma in Lagos State University Teaching Hospital (LASUTH), Ikeja, Lagos state. This study aims to classify bladder carcinoma in this centre according to the World Health Organisation/ International Society of Urological Pathology. Methods: An eight-year retrospective study of all bladder carcinomas specimens that were sent to the department of Pathology and Forensic Medicine, LASUTH between 1st January, 2011 and 31st December, 2018 was done. Relevant data consisting of the age and sex distributions as well as histopathological types were extracted from the departmental information system and filed documents. The data was analysed using the IBM-SPSS version 25.0. Results: There were 87 cases of bladder tumours, out of which 55 (63.2%) were bladder carcinomas. The mean age at diagnosis of bladder carcinomas was 56.9±13.9 years. Sex distribution has male to female ratio of 1: 1. Urothelial carcinoma predominates as the most common histological type. Conclusions: Bladder carcinoma presents most frequently at the 5th decade of life, with a slight male preponderance.